Revisiting the chronology and environmental conditions for the accretion of late Pleistocene-early Holocene Pampean loess (Argentina) - Torre, Gabriela; Gaiero, Diego Marcelo; Oliveira Sawakuchi, André; del Río, Ian; Coppo, Renata (Quaternary Science Reviews)
The present research work reviews the age models of three previously studied loess sections across 700 km in the loess belt of the Pampean region in central Argentina. The loess sections were investigated for the first time through high-resolution luminescence dating in order to determine the chronology of the loess deposits and its temporal correlation with important palaeoclimatic records of the Southern Hemisphere. Reliable estimations of mass accumulation rates (MARs) for loess were used to infer the temporal dust flux variation during the last glacial/interglacial transition in southern South America. The new age models have significant differences compared to the previously published ones of likely Last Glacial Maximum (LGM) ages. The three studied sections showed general bimodal grain-size distributions consistent with multiple sources contributing dust to the Pampas. It is observed that higher MARs values are associated with an increased presence of finer loess. Increases in loess accumulation are coeval with climatic transitions from wetter to drier periods in the Puna-Altiplano Plateau, and high MARs are related to synchronous climatic shifts to humid conditions in the Pampean plain. Contrasting with dust fluxes observed in the more distal palaeoarchives (i.e., the South Atlantic Ocean and the Antarctic ice sheet) the new data suggest increased dust accumulation in the Pampas during the Antarctic Cold Reversal (ACR) and the Holocene. This supports the idea that changes related to atmospheric transport efficiency can better explain dust flux variations observed over glacial/interglacial periods in distant palaeoarchives. Fil: Torre, Gabriela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en Ciencias de la Tierra. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Centro de Investigaciones en Ciencias de la Tierra; Argentina Fil: Gaiero, Diego Marcelo. Consejo Nacional de ...